Realization of the "Care in Education" Concept in Relations with Children and Teaching Staff During the Implementation of the "Writing for Inclusion" Project - Iryna Kohut; Rossella Certini (Firenze University Press, 2022)
The paper presents the state of the art of the European Erasmus Project KA2 - WIN: Writing For Inclusion - dedicated to school inclusion and the use of alternative teaching methodologies such as Digital Storytelling. Starting from a survey on the theme of educational care from a theoretical and pedagogical point of view, the article focuses - in the central parts - on the activities carried out with the students and teachers at the European primary schools involved. The article highlighted the social, as well as educational and cultural implications of the research work carried out by the educational and university institutions involved, with a broad theoretical-methodological reflection which will close, in the coming months, with the assessment of the project itself.